Activity of bisnaphthalimidopropyl derivatives against trypanosoma brucei - Loureiro, I (2016)
Current treatments for African trypanosomiasis are either toxic, costly, difficult to administer, or prone to elicit resistance. This study evaluated the activity of bisnaphthalimidopropyl (BNIP) derivatives against Trypanosoma brucei. BNIPDiaminobutane (BNIPDabut), the most active of these compounds, showed in vitro inhibition in the single-unit nanomolar range, similar to the activity in the reference drug pentamidine, and presented low toxicity and adequate metabolic stability. Additionally, using a murine model of acute infection and live imaging, a significant decrease in parasite load in BNIPDabut-treated mice was observed. However, cure was not achieved. BNIPDabut constitutes a new scaffold for antitrypanosomal drugs that deserves further consideration.